The Effects of Project Based Learning Model toward Students’ Creative Thinking Skill on Civics Subject - Taty Rosiana Koroh; Andriyani Afliani Dua Lehan; Treesly Y. N Adoe; Maxel Koro (Journal Of Teaching And Learning In Elementary Education, 2022)
This study aimed to determine the effects of the Project Based Learning model on students' creative thinking skills in Civics subject on Concepts, Values, Morals and Norms topic. This is a quantitative research, using a quasi-experimental method with a non-equivalent control group design. Subjects of this research were 74 second year students in class A and B of Elementary School Teacher Education Program, Nusa Cendana University. Results were analyzed and tested for its t value through independent sample t test using IBM SPSS Statistics v.16 for Windows. Data analysis result showed that the value of independent sample t-test was 0.020 <0.05. This indicated that there was no enough evidence to accept Ho. Therefore, it could be concluded that there was a positive and significant effect of project based learning model on creative thinking skills in Civics subject comprising Concepts, Values, Morals and Norm material of PGSD Students at Nusa Cendana University, Kupang.